Gestörte Lieferketten – wie reagieren die Betriebe in Deutschland? - Christian Kagerl; Michael Moritz; Duncan Roth; Jens Stegmaier; Ignat Stepanok (Wirtschaftsdienst, 2022)
Der Ausbruch der Coronapandemie 2020 hat die Abhängigkeit der deutschen Wirtschaft von globalen Lieferketten offengelegt. Verzögerungen bei der Zulieferung oder der Ausfall von Vorprodukten infolge eingeschränkter Logistikkapazitäten, geschlossener Grenzen oder einer gestörten Produktion bei Zulieferern hat seitdem bei vielen Betrieben in Deutschland zu Problemen geführt. Mit dem Angriff Russlands auf die Ukraine im Februar 2022 wurde deutlich, dass Lieferketten auch erheblichen geopolitischen Risiken ausgesetzt sind. Die Unternehmen stehen vor der Aufgabe, ihre Zulieferketten resilienter gegen solche Risiken zu machen. – – The outbreak of the coronavirus pandemic in 2020 and the war in Ukraine since 2022 have exposed Germany's dependence on global supply chains. Based on "Establishments in the Covid-19 Crisis", a survey conducted by the Institute for Employment Research (IAB), this paper examines the extent and causes of supply chain disruptions and the responses of establishments in Germany. Our results show that nearly three-quarters of all establishments that report using intermediate inputs have experienced problems with their supply chains in 2022 up until the time of the survey in June. The hospitality, manufacturing, and construction sectors are particularly aff ected. In response to these problems, establishments are diversifying their supply chains by adding new suppliers or replacing existing ones. New suppliers tend to come from geographically closer regions than their predecesors.
Keywords: L14; L23; M11; 330; Lieferkette; Resilienz; Störungsmanagement; Deutschland